The Assessment of Facial Expressions in Piglets Undergoing Tail Docking and Castration: Toward the Development of the Piglet Grimace Scale - Di Giminiani, Pierpaolo; Brierley, Victoria L. M. H.; Scollo, Annalisa; Gottardo, Flaviana; Malcolm, Emma M.; Edwards, Sandra A.; Leach, Matthew C. (Frontiers in Veterinary Science, 2016)
Many piglets are exposed to potentially painful husbandry procedures within the first week of life, including tail docking and castration, without the provision of either anaesthesia or analgesia. The assessment methods used to evaluate pain experienced by piglets are often affected by low specificity and practical limitations, prompting the investigation of alternative methodologies. The assessment of changes in facial expression following a painful event has been successfully applied to several species. The objective of this pilot study was to evaluate the utility of a Grimace Scale applied to neonatal pigs to evaluate pain evoked by tail docking and castration. Eight female piglets, sus scrofa domesticus (Landrace/Large White X synthetic sire line) underwent tail docking and 15 male piglets (75% Large White and 25% Belgian Landrace) were exposed to the castration procedure. Clear images of the faces of the piglets were collected immediately pre- and post-procedure. The images were used by experienced observers to identify Facial Action Units (FAU) which changed in individuals over this period and a scoring scale was depicted in a training manual. A set of randomly selected images were then combined in a scorebook, which was evaluated after training by 30 scorers, blind to the treatment. The scale for most FAU was used with a high level of consistency across all observers. Tail docking induced a significant change (P<0.05) only in the ‘orbital tightening’ Action Unit, whereas no change in any unit was observed in castrated piglets. In this initial stage of development, orbital tightening at least seems to have the potential to be applied to investigate painful conditions in neonatal pigs. Nonetheless, more studies are needed to assess its full effectiveness and to evaluate the influence of possible confounds (e.g. handling stress) on the observed changes in facial expressions.